Experimental study of pseudoelastic behaviour of a Cu Zn AI polycrystalline shape memory alloy under tension-torsion proportional and non-proportional loading tests - Rogueda, C.; Lexcellent, C.; Bocher, L. (Archives of Mechanics, 1996)
Some tension-torsion loading experiments on thin-walled tubular specimens of a Cu Zn Al polycrystalline shape memory alloy have been performed using a special experimental device. Proportional loading tests allow to verify the normality rule for the pseudoelastic strain rate and enable the experimental validation of the thermodynamical model of pseudoelastic behaviour developed by Raniecki et al. Non-proportional loadings show how the pseudoelastic behaviour depends on the chosen loading path. The chosen training path seems to have small effect on the obtained efficiency values which are very high (around 70-80%). A microstructural experimental study must be done to understand the mechanism of formation and reorientation of martensite plates when the stress vector direction changes.